Morphological Analysis of Manggarai Language - Stephanus Mangga (Master Program in Linguistics, Diponegoro University, 2020)
This study was a morphology descriptive analysis of Manggarai language (BM) which was focused on three areas those are language typology based on the level of morphological use namely analytic, synthetic, and polysynthetic; morpheme identification; and morphological process. Therefore the aim of this study was to describe them. Data used in this study were library data which were collected using simak method and introspection method. The data were analyzed using agih method. Besides, there are three main results of the analysis data in this study. The first showed that BM is the analytic language because morphologically words in BM are monomorphemic. The second finding showed that bound morphemes in BM not related to affixation, but they are related to the combination of synonyms and clitictation. The last finding found that there is no affixation in the morphological process, but it is only compound words and reduplication.